Strategic management in the arts - Varbanova, Lidia (Routledge, 2013)
"This book looks at the unique characteristics of cultural organizations and shows readers how to tailor a strategic plan to help these organizations meet their objectives. Including examples, cases, questions and suggestions for further reading, this book is designed to accompany classes on strategic planning, cultural management or arts management"--